Antigens evaluation of Fasciola hepática for three inmulogic methods - Colona, Erasmo (2001)
Excretion–secretion antigens (ESA) of Fasciola hepatica were evaluated in bovine feces samples from endemic area (Andrés Avelino Cáceres, Central Peruvian Andean). We employed ELISA (Fascidig), Indirect hemagglutination (IHA) and Latex agglutination (LA); the results were correlationated with Dennis coproparasitologic method (DC). A number of 106 bovine feces samples were obtained from diferent places of the Region between October and November 1995 (rain time). AES was not detected for LA, the specificity for IHA was 63,6% and the sensibility 35% in relation to DC; the specificity for Elisa (Fascidig) was 68,2% and the sensibility was 60% with regard to DC; and in relation to IHA the specificity was 61,7% and the sensibility 50%. The correlation between ELISA (Fascidig) and DC was significative, it indicates that ELISA is the best method for the fasciolosis diagnostic in the prepatent and patent phases, while DC only is recommended for the patent phase diagnostic. Diagnostic of infection or prevalence for IHA, ELISA and DC was 35,8%, 42,5% and 37,7% respectively. The results indicate that in the investigated area the prevalence of Fasciola hepatica is high. Thanks to this investigation it was possible to evaluate three immunologic methods and to determine the performance of ELISA-Fascidig for the diagnostic of fasciolosis both prepatent and patent infection phases by means of the demonstration of coproantigens.